AGENDA SETTING KEBIJAKAN OMNIBUS LAW DALAM PERSPEKTIF FRAMING PROGRAM TV MATA NAJWA - Putri, Fitra Yuniastri; Wardah, Wardah; Nasrulhaq, Nasrulhaq (Kajian Ilmiah Mahasiswa Administrasi Publik (KIMAP), 2022)
ABSTRACTThis study aimed to analyze and determine the stages of the media agenda on the omnibus law policy setting agenda. The research method used  descriptive qualitative with Robert M Entman's framing analysis on the Mata Najwa episode tv guess work  program . The research informants consisted of workers, practitioners, academics and journalists. Agenda setting contained policy issues as a result of disagreements between actors about the direction of an action that taken by the government. Everett and James Dearing viewed that agenda setting was a linear process consisting of three stages, namely the media agenda, public agenda, and policy agenda. Issues that were considered important in the mass media were certainly considered important by the public, one of which was the omnibus law on job creation. Based on the results of the research, it was known that the media agenda on the omnibus of work copyright law that was broadcast contained 3 aspects, firstly, visibility that the large frequency of the topics aired had an influence on public interest in labor issues which were in the spotlight due to conflicting articles, secondly, audience salience that the relevance of news topics raises various angles. views that could trigger public confusion about the truth of the policy, and the third valance that the way Mata Najwa Program managed its news was able to attract public attention.Keywords: Agenda Setting, Framing, Omnibus Law